Prevalencia de ansiedad, depresión y síndrome burnout en médicos residentes y adscritos al servicio de anestesiología del Hospital General Regional N°1 Charo, Michoacán - López Paniagua, Itzia Mara (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Background: Physicians of various specialties are faced with various processes of adaptation to a new environment and constant learning, which can generate personal, educational and social implications, which can lead to the presence of serious mental health disorders. Studies report prevalence of burnout syndrome in medical specialties between 41-76%, depression of 41.5%, and anxiety of 39%, which represent higher figures than in the rest of the population, with the medical area being vulnerable to these disorders. Objective: to determine the prevalence of anxiety, depression and work stress levels presented by resident physicians and physicians assigned to the anesthesiology service of IMSS Hospital General Regional N° 1, Charo, Michoacán. Material and methods: Cross-sectional, descriptive, observational study in resident physicians and physicians assigned to the anesthesiology service of IMSS Hospital General Regional 1 Charo, Michoacán, in which 64 questions included in the Beck Depression Inventory (BDI-2), Beck Anxiety Inventory and the Maslach Burnout Inventory (MBI-HSS) were applied. Results: 63 medical doctors, 32 anesthesiologists, and 31 residents of the specialty were included in the study. A prevalence of 100% was obtained in anxiety (95% mild), 100% in depression (79% minimal), and 97% in burnout. It was observed that the group with the highest presence of burnout among residents was the third year (25.6% severe burnout). Conclusions: In general, a high prevalence of anxiety, depression, and burnout was observed, in addition to a higher presence in women, third year residents, and a strong association between depression and anxiety with the presence of burnout

Antecedentes: Los médicos de diversas especialidades están enfrentados a diversos procesos de adaptación a nuevo ambiente y aprendizaje constantes, los cuales pueden generar implicaciones personales, educativas y sociales, que pueden llevar a la presencia de trastornos de salud mentales serios. Estudios reportan prevalencias de síndrome de burnout en las especialidades médicas entre 41-76 %, depresión de 41. 5 %, y ansiedad de 39 %, las cuales representan cifras más altas que en el resto de la población, siendo el área médica vulnerable a estos trastornos. Objetivo: determinar la prevalencia de los niveles de ansiedad, depresión y estrés laboral que presentan los médicos residentes y médicos adscritos del servicio de anestesiología del IMSS hospital general regional N°1, Charo, Michoacán. Material y métodos: Estudio transversal, descriptivo, observacional en médicos residentes y médicos adscritos del servicio de anestesiología del IMSS Hospital General Regional #1 Charo, Michoacán, en los cuales se aplicaron 64 preguntas incluidas en Inventario de Depresión de Beck (BDI-2), Inventario de ansiedad de Beck y el inventario de Maslach Burnout (MBI -HSS). Resultados: Se incluyeron 63 médicos en el estudio, 32 anestesiólogos y 31 residentes de la especialidad, se obtuvo una prevalencia del 100 % en ansiedad (95 % leve), 100 % en depresión (79 % mínima) y un 97 % en burnout, se observó que el grupo con mayor presencia de burnout entre los residentes fue el tercer año (25.6 % burnout severo). Conclusiones: en general se observó una alta prevalencia de ansiedad, depresión y burnout, además de una presencia mayor en las mujeres, residentes de tercer año y una asociación fuerte entre depresión y ansiedad con la presencia de burnout.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Anestesiología
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19125; info:eu-repo/classification/cti/3; FCMB-E-2025-0237; Ansiedad; Depresión; Estrés laboral